Enhancing biomass and lipid productivities of Haematococcus pluvialis for industrial raw materials products - Övgü Gencer; Gamze Turan (Biotechnology for Biofuels and Bioproducts)
Abstract For biofuels and nutraceuticals, the green microalga Haematococcus pluvialis (Chlorophyceae) is a prospective source of biomass and lipids. This study examined how biomass production and lipid accumulation were affected by temperature (10 °C, 20 °C, and 30 °C) and potassium nitrate (KNO₃) concentrations (0.41 g/L, 0.31 g/L, 0.21 g/L, 0.10 g/L, and 0). The findings showed that the largest biomass (0.665 ± 0.200 g/L) was produced at a potassium nitrate concentration of 0.21 g/L at 20 °C, whereas the highest lipid content (46.31 ± 0.026% dry weight) was produced at a temperature without nitrate. Notably, a balanced result was obtained with a modest nitrate content (0.10 g/L) at 20 °C, yielding significant biomass (0.560 ± 0.136 g/L) and lipids (40.30 ± 0.012% dry weight). These results highlight how crucial it is to optimize cultivation settings in order to increase H. pluvialis's dual productivity, offering important new information for its industrial-scale use. By adjusting growing conditions, this research helps meet the need for renewable resources worldwide by promoting the production of high-value bioproducts and sustainable, commercially viable algae-based biofuels.